The generic intertext of psalms in the poetry of Marina Tsvetaeva (1892-1941) - Ossipow Cheang, Sarah (2008)
This study investigates the presence of the genre of psalms in Tsvetaeva's poetry by means of Alastaire Fowler's theory of the historical persistence of literary genres throughout history. The main argument is that in her intertextual use of psalms Tsvetaeva develops further some of their typical features such as the expression of bafflement at God's passivity or an over-familiarity in addressing God; although these features are already present in psalms, they are not given a full-blown realisation because of the religious restrictions reigning at the time and context in which they were written.